Identifying sustainable coexistence potential by integrating willingness-to-coexist with habitat suitability assessments. (March 2023) - Vogel, Susanne Marieke; Vasudev, Divya; Ogutu, Joseph O.; Taek, Purity; Berti, Emilio; Goswami, Varun R.; Kaelo, Michael; Buitenwerf, Robert; Munk, Michael; Li, Wang; Wall, Jake; Chala, Desalegn; et al.
Abstract: Persistence of species in the Anthropocene depends on human willingness-to-coexist with them, but this is rarely incorporated into habitat suitability or conservation priority assessments. We propose a framework of sustainable coexistence potential that integrates human willingness-to-coexist with habitat suitability assessments. We demonstrate its applicability for elephants and rhinos in the socio-ecological system of Maasai Mara, Kenya, by integrating spatial distributions of peoples' willingness-to-coexist based on Bayesian hierarchical models using 556 household interviews, with socio-ecological habitat suitability mapping validated with long-term elephant observations from aerial surveys. Willingness-to-coexist was higher if people had little personal experience with a species, and strongly reduced by experiencing a species as a threat to humans. The sustainable coexistence potential framework highlights areas of low socio-ecological suitability, and areas that require more effort to increase positive stakeholder engagement to achieve long-term persistence of large herbivores in human-dominated landscapes.